Tinjauan K3 pada Pembangunan Gedung Mall Pelayanan Publik Kabupaten Garut - Ida Farida; Aji Samsul Muarif (Jurnal Konstruksi, 2025)
Garut Regency is one of the cities in West Java and is equipped with a wide range of infrastructure and facilities. Among these is the construction of the Public Service Mall building in Garut Regency. However, this project has highlighted the construction industry’s poor track record in terms of occupational safety and health. The high-risk nature of the project site demands optimal stamina from the workers involved. Therefore, Occupational Safety and Health (OSH) is a critical aspect that must be continuously upheld. Given the complexity of the issues involved, this thesis aims to examine OSH practices in the construction of the Public Service Mall in Garut Regency.The research methodology used in this study is the Analytical Hierarchy Process (AHP), which is employed to determine a ratio scale from several pairwise comparisons, whether discrete or continuous. The study identified key factors contributing to workplace accidents: worker attitude, equipment mobilization, and site clearing. The most dominant factor leading to on-site accidents was foundation work, due to frequent interactions between workers and various tools and machinery during this phase.To address this issue, a worksheet needs to be developed that outlines guidelines for the use of Personal Protective Equipment (PPE) in the work area. With this worksheet, workers will be able to easily read and understand the potential hazards they may face if PPE is not used. This will help raise awareness among workers of the importance of PPE in ensuring their safety on the job.